(untitled) (Revista de Ciências Agroveterinárias, 2023)
Pesticide use is a widespread practice in agricultural production for pest control. The use of these products must adopt Good Agricultural Practices; therefore, the food is expected to be according to the current parameters. For this, the National Program for the Control of Residues and Contaminants of the Ministry of Agriculture and Livestock created a diagnosis of the products’ quality. In this way, the program carried out pesticide analyses to evaluate the conformity of products of plant origin. From the analyzed products, fruits with broad commercialization and production in a state with more analyses were segregated. Based on these data, the banana, potato, apple, tomato, and grape results in the Rio Grande do Sul state (Southern Brazil) were analyzed and interpreted. This survey was conducted from 2016 to 2020, and data were compiled to assess the conformity of fresh vegetables. Samples with residual levels of pesticides above the maximum reference limit for the crop or with residual not allowed for the crop no-tolerance were considered non-conformance. The overall compliance rate for the highlighted vegetables was greater than 95%. The data were similar to countries with rigorous monitoring and application standards for this chemical hazard. Most of the non-conformities occurred due to the presence of residues above the maximum reference limit for the crop, especially due to the presence of insecticides from the chemical groups organophosphates and pyrethroids. These results show that food produced and consumed in Brazil has quality characteristics similar to those in developed countries. Illustrating that the food consumed by the population is safe. To obtain better results, technical assistance to farmers is essential, aiming to reduce the incidence of residues above the Maximum Limit for the crop.